Оптимізація параметрів мікроклімату в навчальних закладах з системами локальної рекуперації повітря - Савеленко, І. В.; Петрова, К. Г.; Котиш, А. І.; Сіріков, О. І.; Savelenko, I.; Petrova, K.; Kotysh, А.; Sirikov, O. (ЦНТУ, 2023)
Розроблена система автоматичного керування локальною рекуперацією повітря, яка гарантує оптимальні параметри мікроклімату у приміщеннях навчальних закладів. Застосовано комп'ютерне імітаційне моделювання системи керування мікрокліматом на основі температури та концентрації СО2. Виявлено переваги запропонованої системи, яка зменшила тривалість періоду з перевищенням максимально допустимого рівня концентрації СО2 на 49,5%, а також знизила значення концентрації СО2 на 13,1%, при відповідних межах температури. The aim is to develop an automatic local air recovery system to ensure thermal comfort and the normative composition of the air environment in educational institution premises. Improving the efficiency of local air recovery systems while maintaining optimal microclimate parameters is possible through the enhancement of automatic control systems for local recovery devices. An automatic air local recovery control system has been developed, which guarantees optimal microclimate parameters in educational institution premises. Computer simulation modeling has been applied to control the microclimate system based on temperature and CO2 concentration. The advantages of the proposed system have been identified, which reduced the duration of exceeding the maximum allowable level of CO2 concentration by 49.5% and decreased the CO2 concentration by 13.1% within the specified temperature limits.
Optimization of Microclimate Parameters in Educational Institutions with air Local Recovery Systems
Keywords: система локальної рекуперації повітря; мікроклімат приміщення; система автоматичного керування; якість повітря; local air recovery; microclimate; automatic control system; air quality